2013
DOI: 10.1021/mp400498n
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Miscibility and Molecular Mobility of Nifedipine-PVP Amorphous Solid Dispersions Using Solid-State NMR Spectroscopy

Abstract: Solid-state NMR (SSNMR) (1)H T1 and T1ρ relaxation times were used to evaluate the miscibility of amorphous solid dispersions of nifedipine (NIF) and polyvinylpyrrolidone (PVP) prepared by three different methods: melt quenching in the typical lab setting, spray drying and melt quenching in the NMR rotor while spinning. Of the five compositions prepared by melt quenching in the lab setting, the 95:5 and 90:10 NIF:PVP (w:w) amorphous solid dispersions were not miscible while 75:25, 60:40, and 50:50 NIF:PVP disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(170 citation statements)
references
References 51 publications
2
166
1
1
Order By: Relevance
“…This was probably due to the presence of amorphous clusters in the bulk samples which were smaller than the detection limit of DSC. It has been reported that amorphous clusters smaller than 30 nm, even tens of microns (39), generally could not be distinguished by DSC and resulted in misleading conclusions as to the nature of a molecularly dispersed drug (16). These conclusions highlight the significance of Raman spectroscopy as a technique to examine the hydrophobic interactions between the drug and polymeric matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was probably due to the presence of amorphous clusters in the bulk samples which were smaller than the detection limit of DSC. It has been reported that amorphous clusters smaller than 30 nm, even tens of microns (39), generally could not be distinguished by DSC and resulted in misleading conclusions as to the nature of a molecularly dispersed drug (16). These conclusions highlight the significance of Raman spectroscopy as a technique to examine the hydrophobic interactions between the drug and polymeric matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of intermolecular interaction is a key factor governing the physical stabilization of solid dispersions and it may be related to the miscibility of the drug in the polymer matrix (7). To date, there have been several attempts to apply analytical methods to characterize drug-polymer miscibility, e.g., differential scanning calorimetry (DSC) (3,(8)(9)(10)(11)(12)(13)(14)(15)(16), infrared spectroscopy (IR) (8)(9)(10)(11)(12)(13)(17)(18)(19), solid state-nuclear magnetic resonance (ss-NMR) (14,16), Xray powder diffractometry (XRD) (10), X-ray photoelectron spectroscopy (XPS) (14) and Raman spectroscopy (15,(19)(20)(21)(22)(23). The strength of intermolecular hydrogen bonding between drug and polymer in a solid dispersion has been investigated by IR based on the peak position (12,13,18) and peak height ratio (13,17).…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al reported that the 13 C chemical shift of the carbonyl peak of PVP in the 95:5 (w/w) nifedipine/PVP solid dispersion appears 0.8 ppm lower when compared with that of PVP intact. 35 It was suggested that, in solid dispersions with high drug loadings, some of the nifedipine is monomolecularly dispersed in the PVP matrix, while some of the nifedipine forms small domains. Thus, it suggests that at low drug loadings below 10 %, almost all the DPH is monomolecularly dispersed throughout the S100 matrix, and the DPH interacts strongly with the S100 polymer.…”
Section: Miscibility Of Dph and S100 Evaluated By Solid-state Nmr Spementioning
confidence: 99%
“…The effective diffusion range was calculated to be 2-5 nm according to typical   of 5-50 ms, which is significantly smaller than the T 1 of 5-50 s. Hence, the miscibility on the smaller scale of 2-5 nm is evaluated by 1 H-T  measurements compared with the scale of approximately 20-50 nm by 1 H-T  . 34,35,37 In this experiment, 13 C detected-1 H-T  measurements using CP was performed that gives the 1 H-T  of each 13 C peaks. Table 1a shows the 1 H-T  of the DPH/S100 SPD 75 %.…”
Section: Miscibility Of Dph and S100 Evaluated By Solid-state Nmr Spementioning
confidence: 99%
See 1 more Smart Citation